Implementasi Program Penilaian Kepatuhan terhadap Standar Pelayanan Publik oleh Ombudsman Republik Indonesia Perwakilan Jawa Timur - Irawan, Fanny Andrianto; Wahyudi, Kalvin Edo (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to describe the implementation of compliance assessments with public service standards by the Republic of Indonesia Ombudsman representing East Java. The research method uses descriptive qualitative. Assessing compliance with public service standards is the duty and authority of the Ombudsman of the Republic of Indonesia as the supervisor of public services. This program for assessing compliance with public service standards has been designed as a form of supervision by the Ombudsman of the Republic of Indonesia regarding public service standards. This compliance assessment program is used to ensure that in public services there are no more maladministrative activities so that service recipients can be provided with the best service in order to provide a feeling of comfort and security to service recipients. The implementation of the compliance assessment carried out by the Ombudsman representative for East Java has been very good although there are still slight deficiencies in terms of employee resources in carrying out the compliance assessment. It can be concluded that the implementation carried out by the Ombudsman representing East Java has gone very well.